"Dogmatic and apologetic" method and the problem of foundation оf religious and Christian knowledge in the works of P. Svetlov - Pecheranskyy, Igor (Skhid, 2013)
The article deals with the emperical and synthetic approach to the creating of the theory of religious and Christian knowledge in the context of apologetic studio of Pavlo Yakovlevych Svetlov, a representative of Kyiv Academic Philosophy of the 19th and early 20th century.